A review of the botany, phytochemistry, traditional uses, pharmacology, toxicology, and quality control of the Astragalus memeranaceus - Wang, Panpan; Wang, Zhen; Zhang, Zhanping; Cao, Huiyan; Kong, Lingyang; Ma, Wei; Ren, Weichao (Frontiers in Pharmacology, 2023)
It has long been used as an ethnomedicine in the Russian Federation, Mongolia, Korea, Kazakhstan, and China. It was first recorded in the Shennong Ben Cao Jing and includes the effects of reinforcing healthy qi, dispelling pathogenic factors, promoting diuresis, reducing swelling, activating blood circulation, and dredging collaterals. This review systematically summarizes the botanical characteristics, phytochemistry, traditional uses, pharmacology, and toxicology of Astragalus to explore the potential of Huangqi and expand its applications. Data were obtained from databases such as PubMed, CNKI, Wan Fang Data, Baidu Scholar, and Google Scholar. The collected material also includes classic works of Chinese herbal medicine, Chinese Pharmacopoeia, Chinese Medicine Dictionary, and PhD and Master's theses. The pharmacological effects of the isoflavone fraction in Huangqi have been studied extensively;The pharmacological effects of Huangqi isoflavone are mainly reflected in its antiinflammatory, anti-tumor, anti-oxidant, anti-allergic, and anti-diabetic properties and its ability to treat several related diseases. Additionally, the medicinal uses, chemical composition, pharmacological activity, toxicology, and quality control of Huangqi require further elucidation.Here, we provide a comprehensive review of the botany, phytochemistry, traditional uses, pharmacology, toxicology, and quality control of Astragalus to assist future innovative research and to identify and develop new drugs involving Huangqi.